An 18-hole round of golf acutely elevates serum interleukin-6 and brain-derived neurotrophic factor concentration - a pilot study - Yoshinori Yasuoka; Takeshi Nakamura; Yasunori Umemoto; Tokio Kinoshita; Sven P. Hoekstra; Keisuke Hoshiai; Hiroshi Ohko; Masahiro Abo; Fumihiro Tajima (Japanese Society of Physical Fitness and Sports Medicine, 2022)
This study investigated the acute effect of an 18-hole round of golf on serum interleukin-6 (IL-6) and brain-derived neurotropic factor (BDNF) concentration. Nine young, healthy males, unaccustomed to playing golf, completed an 18-hole round of golf (course length: 5,807 m.). Blood samples were collected prior to, immediately after and 1 h following completion of the exercise session. Interleukin-6 and BDNF, as well as creatine kinase (CK) and myoglobin concentrations were analysed in serum, while adrenaline concentrations were assessed in plasma. The participants completed the course in 303 ± 4 min. Serum IL-6 and BDNF concentrations were respectively elevated 8.6 ± 5.4-fold and 1.2 ± 0.3-fold immediately post-exercise (IL-6 p = 0.008; BDNF p = 0.038). Creatine kinase (p = 0.008), myoglobin (p = 0.011) and adrenaline concentrations (p = 0.038) were also acutely elevated following completion of the golf course. Creatine kinase and myoglobin concentrations were significantly correlated with the acute increase in IL-6 concentration post-exercise (r = 0.70 p = 0.034, r = 0.79 p = 0.012, respectively), while no such relationship was found for BDNF concentration. (r = 0.37 p = 0.333, r = 0.08 p = 0.833, respectively). An 18-hole round of golf was found to acutely elevate IL-6 and BDNF concentration in young, healthy males unaccustomed to playing golf. The correlation of CK and myoglobin with the acute IL-6 response suggests that muscle damage may have influenced the acute increase in this marker. Together, this pilot-study indicates that golf may be promoted as an accessible, low-intensity activity to acutely elevate markers suggested to stimulate improvements in metabolic health and cognitive function.